2022
DOI: 10.3390/en15176471
|View full text |Cite
|
Sign up to set email alerts
|

Particle Number Emission from Vehicles of Various Drives in the RDE Tests

Abstract: In this study, the authors assessed the road emissions of several passenger cars using specialised instrumentation, of the PEMS type, to measure particle number emissions in real traffic conditions. The tests were performed on a RDE test route developed and compliant with EU guidelines. The results of the tests were discussed in terms of the direct (created in the internal combustion engine) emission of particulate matter in various road conditions. Additionally, an index was determined that characterizes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…To improve the emissions and fuel consumption that occur when driving under road conditions, a new WLTP (World Harmonised Light Duty Procedure) driving test procedure was created [52]. With the new procedure, in addition to the determination of emissions during controlled driving tests with a chassis dynamometer, real driving emission (RDE) road tests are also carried out using mobile emission measurement systems -PEMS (Portable Emissions Measurement System) [53,54,55].…”
Section: Main Components Of Vehicle Exhaustmentioning
confidence: 99%
“…To improve the emissions and fuel consumption that occur when driving under road conditions, a new WLTP (World Harmonised Light Duty Procedure) driving test procedure was created [52]. With the new procedure, in addition to the determination of emissions during controlled driving tests with a chassis dynamometer, real driving emission (RDE) road tests are also carried out using mobile emission measurement systems -PEMS (Portable Emissions Measurement System) [53,54,55].…”
Section: Main Components Of Vehicle Exhaustmentioning
confidence: 99%
“…During the heating of individual components and fluids, significant amounts of pollutants, such as nitrogen oxides, carbon monoxide, solid particles, and hydrocarbons, are emitted [173,174]. For example, in the study of Giechaskiel et al [175], CO, HC, and NO x emissions are higher for temperatures below 5 • C compared to tests conducted at 23 • C according to the WLTP.…”
Section: Cold Start and Weather Conditionsmentioning
confidence: 99%
“…The heating period of individual vehicle systems depends on weather conditions. Low temperatures extend and intensify the cold-start effect [173].…”
Section: Cold Start and Weather Conditionsmentioning
confidence: 99%
“…In [13], the authors stated that for motor vehicles after a combustion-engine cold-start, the characteristic feature is the increased concentration of the number of particles with a diameter of about 100 nm. The tests carried out in real driving conditions confirmed that the exhaust emissions of particles with diameters smaller than 23 nm were significant in conventional vehicles, regardless of the engine type (petrol or diesel).…”
Section: Exhaust Emission Tests-state Of Knowledgementioning
confidence: 99%